2020
DOI: 10.1109/access.2020.2970533
|View full text |Cite
|
Sign up to set email alerts
|

Point Cloud Features-Based Kernel SVM for Human-Vehicle Classification in Millimeter Wave Radar

Abstract: Human-vehicle classification plays an important role in advanced driver assistance systems (ADAS). The use of millimeter wave (mmWave) radar sensor in human-vehicle classification algorithms is of great significance since the sensor maintains to be robust in severe weather (e.g. fog, snow, etc.). To improve classification accuracy under complex scenes of autonomous driving, a new mmWave radar point cloud classification algorithm is proposed in this paper, which realizes human-vehicle classification employing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 35 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…Although FFT processes data of multiple dimensions, Range FFT data including range information and RDI including velocity information are calculated [ 33 ]. The frequency of IF signal is , the range resolution is , the maximum unambiguous velocity is and the velocity resolution is , where is the wave length of the radar signal, and is the number of chirps.…”
Section: Background Theory and Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FFT processes data of multiple dimensions, Range FFT data including range information and RDI including velocity information are calculated [ 33 ]. The frequency of IF signal is , the range resolution is , the maximum unambiguous velocity is and the velocity resolution is , where is the wave length of the radar signal, and is the number of chirps.…”
Section: Background Theory and Proposed Methodsmentioning
confidence: 99%
“…Radar point cloud data not only contains almost all the aforementioned features but also can directly indicate the spatial locations of the targets, and they are receiving more attention. However, most of these research investigations are focused only on feature extraction and recognition after obtaining point clouds without paying much attention to the generation of the point cloud [15,[32][33][34][35][36]. This causes inaccurate results because it is well known that the quality of the generated point cloud has a significant effect on the accuracy and effectiveness of the subsequent data process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the boundaries of the point clouds can be used as significant features for classification. The 2D point cloud boundary extraction methods include the rectangular box model [20], confidence ellipse model, and convex hull model [21]. Because the RADAR point cloud is distributed in 3D space, we used a 3D bounding box with orientation to extract the shape features, as shown in Figure 5.…”
Section: Proposed Classification Methodsmentioning
confidence: 99%
“…Lorente et al [24] have shown that LIDAR and Time-of-flight (TOF) cameras can be used for point cloud acquisition and that such information can be, with the use of deep learning methods, applied for pedestrian detection. A millimeter-wave radar was used for a similar application, where Zhao et al [25] proposed a point cloud classification algorithm for human-vehicle classification in advanced driver assistance systems (ADAS). Aside from various imaging technologies, there are also examples of passive, nonimaging solutions for sensing a human presence.…”
Section: Pedestrian Detectionmentioning
confidence: 99%